Strategies and measurement for global health governance assessment: a 5-years mixed review. (13th November 2019) - Damiani, G; Pettinicchio, V; Markovic, R; Rosi, L
Abstract: : Global health governance is defined as the use of institutions, rules and processes "to deal with challenges to health that require cross-border collective action to be addressed effectively". Several studies on this have been published, but there is no consensus about the measure of its various aspects. The aim of this study was to search for strategies used by healthcare systems to evaluate their care in global settings and for shared indicators to assess global health governance worldwide. This systematic analysis of qualitative and quantitative studies was conducted according to the Population-Intervention-COntext model and the Population-Intervention-Comparison-Outcome models, using search string "global health and governance and assessment", from 2014 to 2018 (in biennium 2013-14 WHO and others identified health governance as a global priority). Articles that reported quantitative and/or qualitative evaluation on global health governance were included. Outcomes were screened by title and abstract, and then by full texts in order to assess eligibility. From a total of 98, six studies met inclusion criteria. 4 main strategies of global health governance were identified: intersectoral policies (demographic factors, sanitation practices, housing characteristics and social behaviors); food and nutrition, caring to strengthen country-owned governance capacity (high levels of governance are associated with signing up initiatives for undernutrition prevention, OR = 30); disability and rehabilitation, crucial for realization of the right to health; risk factors control and non-communicable disease prevention (tobacco control). Two set of indicators were found: an expert-informed framework for assessing rehabilitation and a set of primary data sources to evaluate nutrition in fragile countries. Although lots of evidence in literature about globalization, only few areas are adequately measured. Literature about this topic should pay attention to assessment. Key messages: In literature, four local areas were identified having perspective of global health governance: intersectoral policies, nutrition, rehabilitation and non-communicable disease prevention. For two of these areas, nutrition and rehabilitation, shared patterns of indicators were found, from primary data sources and expert consensus.